بعض انعكاسات الغش في امتحانات الثانوية العامة وسبل مواجهتها - حمدان، سحر محمد أحمد (جامعة المنصورة - مركز تطوير الأداء الجامعي, 2020)
هدف البحث الوقوف على بعض انعكاسات الغش في امتحانات الثانوية العامة وكيفية مواجهتها وكيفية مواجهتها، واستخدم البحث المنهج الوصفي، وتم تطبيق الاستبانة على عينة مكونة من (1989) من من الطلاب والمديرين والمعلمين القائمين على رأس العمل بمدارس التعليم الثانوي العام بمحافظة الدقهلية، وتوصل البحث إلى مجموعة من الانعكاسات السلبية للغش في امتحانات الثانوية العامة أبرزها: تكاسل الطلبة وعزوفهم عن استذكار الموضوعات الدراسية، زيادة احتمالية توجه الطلاب نحو إلى إهمال الدراسة مستقبلا، ضعف معنويات الطلاب المجتهدين وزيادة شعورهم بفقدان الثقة فيما حولهم، غرس الكسل وعدم الاجتهاد والإهمال في الطلاب.
The aim of the research is to identify some of the repercussions of cheating in high school exams, how to face them, and how to face them. The research used the descriptive approach, and the questionnaire was applied to a sample made up of (1989) from students, managers, and teachers who are at work at the general secondary education schools in Dakahlia governorate, and the research has reached A group of negative repercussions of cheating in the high school exams, the most prominent of which are: students' laziness and their reluctance to recall study subjects, the increased probability of students heading towards future study neglect, poor morale of diligent students and an increase in their sense of loss of confidence around them, planting laziness, lack of diligence and neglect in students.
Keywords: الاختبارات التحصيلية -- الثانوية العامة -- ظاهرة الغش -- القيم السلوكية